Chemical composition of Urochloa and Megathyrsus maximus cultivars under tropical humid forest conditions - Garrido-Ricoveri, Fabio; Román , María; Maldonado-Cruz, Rover; Cordero , Luis; Fossi , Alonso; Vergara, Juan; Razz, Rosa; Ortega, Jorge (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2026)
Urochloa and Megathyrsus maximus comprise the most widely sown grasses in Venezuela, and their composition is influenced by management practices and the rainfall regime in the region. The chemical composition of seven grass cultivars (CV) was evaluatedduring the dry and rainy seasons (SE) under two (4 and 6 weeks) defoliation frequencies (DF) in tropical humid forest conditionsof the Catatumbo municipality, Zulia state, Venezuela. Dry Matter DM), Ash (ASH), Ether Extract (EE), Crude Protein (CP) andCrude Fiber (CF) were measured. A randomized complete block design with a split-plot arrangement and four replications percultivar was used. Highly significant effects (p<0.01) of SE were observed on ASH, EE and CF contents. Defoliation frequencysignificantly affected (p<0.01) all evaluated variables, with notable CP contents in cultivars BR02/0465 (10.36 %) and CIAT 606(10.17 %). Considering SE, CV and DF together, highly significant effects (p<0.01) were determined on EE contents of M. maximus cv.Tanzania (2.59 %) and CIAT BR02/0465 (2.39 %) during the dry SE at DF 4 weeks. Regarding CF, significant decreases (p<0.01) wererecorded as the age advanced from 4 to 6 weeks in cultivars Tanzania (26.87 % to 26.66 %), BR02/0465 (25.03 % to 21.68 %) and MulatoII (24.81 % to 20.46 %). From a bromatological perspective, the evaluated cultivars demonstrated high nutritional value, particularlyCIAT BR02/0465, identifying it as a promising option for the tropical humid forest of El Guayabo.